Hukum Islam Dalam Perkawinan Di Indonesia: Telaah Sosial Budaya Dan Implikasinya - S, Samsidar; M, Marilang; Akmal, Andi Muhammad (Institut Agama Islam Negeri (IAIN) Bone, 2025)
Marriage in the context of Islamic law in Indonesia has an important position and is an integral part of religious, socio-cultural and legal life in society. Islamic law regulates various aspects of marriage, including harmony, conditions, rights and obligations of husband and wife. In Indonesia, the application of Islamic law in marriage is regulated in Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. The marriage process in Islamic law includes the consent of both parties, the presence of a guardian, witnesses and a dowry as one of the conditions for the validity of the marriage. However, the practice of Islamic law in marriage is often influenced by the diverse cultural and social contexts in Indonesia, which can lead to differences in interpretation and implementation in various regions. This research aims to analyze how Islamic law is implemented in marriage in Indonesia, the challenges faced, and its impact on society. Results The implementation of Islamic law in marriage in Indonesia has many complex aspects, with significant challenges. Although there is potential to provide protection and justice, successful implementation is highly dependent on community understanding, legal interpretation, and support from relevant institutions. The impact on society can be positive or negative, depending on how this law is applied and understood in the existing social and cultural context. By understanding this legal framework, it is hoped that it can provide deeper insight into the role of Islamic law in strengthening family institutions and maintaining social harmony in society. Indonesia.Perkawinan dalam konteks hukum Islam di Indonesia memiliki kedudukan yang penting dan menjadi bagian integral dari kehidupan agama, sosial budaya dan hukum di masyarakat. Hukum Islam mengatur berbagai aspek perkawinan, termasuk rukun, syarat, hak dan kewajiban suami istri. Di Indonesia, penerapan hukum Islam dalam perkawinan diatur dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Kompilasi Hukum Islam. Proses perkawinan dalam hukum Islam mencakup persetujuan kedua belah pihak, adanya wali, saksi dan mahar sebagai salah satu syarat sahnya perkawinan. Meskipun demikian, praktik hukum Islam dalam perkawinan seringkali terpengaruh oleh konteks budaya dan sosial yang beragam di Indonesia, yang dapat menimbulkan perbedaan interpretasi dan pelaksanaan di berbagai daerah. Penelitian ini bertujuan untuk menganalisis bagaimana hukum Islam diimplementasikan dalam perkawinan di Indonesia, tantangan yang dihadapi, serta dampaknya terhadap masyarakat.Hasil Implementasi hukum Islam dalam perkawinan di Indonesia memiliki banyak aspek yang kompleks, dengan tantangan yang signifikan. Meskipun ada potensi untuk memberikan perlindungan dan keadilan, keberhasilan implementasinya sangat tergantung pada pemahaman masyarakat, interpretasi hukum, dan dukungan dari lembaga terkait. Dampaknya terhadap masyarakat bisa positif atau negatif, tergantung pada bagaimana hukum ini diterapkan dan dipahami dalam konteks sosial dan budaya yang ada Dengan memahami kerangka hukum ini, diharapkan dapat memberikan wawasan yang lebih mendalam tentang peran hukum Islam dalam memperkuat institusi keluarga dan menjaga keharmonisan sosial di masyarakat Indonesia